PERBEDAAN RATA-RATA LINGKAR PERUT, KONSUMSI KARBOHIDRAT, DAN NATRIUM LANSIA HIPERTENSI PRIMER STAGE 1 DENGAN STAGE 2 PUSKESMAS ARJUNO KOTA MALANG - Agatha Derta Donira; Diah Mulyawati Utari (Jurnal Sehat Mandiri, 2021)
The risk factors for hypertension are abdominal obesity, carbohydrate and sodium intake. The purpose of this study to determine the average difference in abdominal circumference, carbohydrate, and sodium consumption in elderly patients with stage 1 primary hypertension and stage 2 in the Arjuno Public Health, Malang City. The research method used a cross sectional design, during November 2016. The sampling technique used purposive sampling, the inclusion criteria were aged >55 years and suffering from primary hypertension. Abdominal circumference was measured using metlin, carbohydrate and sodium consumption obtained from a 1x24 hour recall interview. Data analysis used independent t test and Mann Whitney. The results showed that there was a difference in the average sodium consumption of the elderly with stage 1 primary hypertension and stage 2 from a significant p-value (p=0,032). Meanwhile, abdominal circumference and carbohydrate intake did not show an average difference between the elderly with primary hypertension stage 1 and stage 2 (p=0,580; p=0,332).The results showed that there was no difference in the average abdominal circumference and carbohydrate consumption with the hypertension stage, but there was an average difference between sodium consumption in the elderly with primary hypertension stage 1 and stage 2. It is recommended to provide education to the elderly in the work area of ​​the Arjuno Health Center Malang City about a balanced nutritional diet, low in carbohydrates, and low in sodium to keep his blood pressure more stable. Further research to widen the age range towards a younger and increase the number of samples.